The Artificial Heart's Threat to Others - Jonsen, Albert R. (The Hastings Center report, 1986)
A member of the two federal advisory panels on artificial hearts reflects that the nuclear-powered artificial heart, had it been developed, would have posed a physical threat to others. Today's artificial heart poses a different threat. Because of the high costs, many people may be deprived of access to other forms of medical care and other social goods.